Copper-61 is an advantageous alternative to gallium-68 for PET imaging of somatostatin receptor-expressing tumors: a head-to-head comparative preclinical study - Basaco Bernabeu, Tais; Mansi, Rosalba; Del Pozzo, Luigi; Gaonkar, Raghuvir Haridas; McDougall, Lisa; Johayem, Anass; Blagoev, Milen; De Rose, Francesco; Jaafar-Thiel, Leila; Fani, Melpomeni (Frontiers in Nuclear Medicine, 2024)
Background Gallium-68 positron emission tomography (68Ga-PET) with the two registered somatostatin analogs, [68Ga]Ga-DOTA-Tyr3-octreotide ([68Ga]Ga-DOTA-TOC) and [68Ga]Ga-DOTA-Tyr3-octreotate ([68Ga]Ga-DOTA-TATE), where DOTA = 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid, is routinely used for imaging of somatostatin receptor (SST)-expressing tumors. We investigated copper-61 (61Cu) as an alternative radiometal for PET imaging of SST-expressing tumors. Compared to gallium-68, copper-61 (t1/2 = 3.33 h, Eβ+max = 1.22 MeV) can be produced on a large scale, enables late time point imaging, and has the therapeutic twin copper-67. Herein, DOTA-TOC and 1,4,7-triazacyclononane,1-glutaric acid-4,7-acetic acid (NODAGA)-TOC were labeled with copper-61 and compared with the clinically used [68Ga]Ga-DOTA-TOC. Methods [61Cu]CuCl2 was produced from an irradiated natural nickel target. DOTA-TOC and NODAGA-TOC were labeled with [61Cu]CuCl2 in ammonium acetate buffer so to achieve a reaction pH of 5–6 and a temperature of 95°C for DOTA-TOC or room temperature for NODAGA-TOC. The radioligands were evaluated head-to-head in vitro using human embryonic kidney (HEK)-SST2 cells (affinity, binding sites, cellular uptake, and efflux) and in vivo using HEK-SST2 xenografts [PET/computed tomography (CT) imaging, biodistribution, and pharmacokinetics] and compared with [68Ga]Ga-DOTA-TOC, which was prepared using a standard procedure. Dosimetry estimates were made for [61Cu]Cu-NODAGA-TOC. Results [61Cu]Cu-DOTA-TOC and [61Cu]Cu-NODAGA-TOC were prepared at an apparent molar activity of 25 MBq/nmol with radiochemical purities of ≥96% and ≥98%, respectively. In vitro, both presented a sub-nanomolar affinity for SST2 (IC50 = 0.23 and 0.34 nM, respectively). They were almost entirely internalized upon binding to SST2-expressing cells and had similar efflux rates at 37°C. In vivo, [61Cu]Cu-DOTA-TOC and [61Cu]Cu-NODAGA-TOC showed the same accumulation in SST2-expressing tumors. However, PET/CT images and biodistribution analyses clearly showed an unfavorable biodistribution for [61Cu]Cu-DOTA-TOC, characterized by accumulation in the liver and the abdomen. [61Cu]Cu-NODAGA-TOC displayed favorable biodistribution, comparable with [68Ga]Ga-DOTA-TOC at 1 h post-injection (p.i.). Notwithstanding, [61Cu]Cu-NODAGA-TOC showed advantages at 4 h p.i., due to the tumor retention and improved tumor-to-non-tumor ratios. The effective dose (2.41 × 10−3 mSv/MBq) of [61Cu]Cu-NODAGA-TOC, but also the dose to the other organs and the kidneys (9.65 × 10−2 mGy/MBq), suggested a favorable safety profile. Conclusion Somatostatin receptor 61Cu-PET imaging not only matches the performance of 68Ga-PET at 1 h p.i. but has advantages in late-time imaging at 4 h p.i., as it provides improved tumor-to-non-tumor ratios. [61Cu]Cu-NODAGA-TOC is superior to [61Cu]Cu-DOTA-TOC in vivo. The use of the chelator NODAGA allows quantitative labeling with copper-61 at room temperature and enables the straightforward use of a kit formulation for simple manufacturing in medical centers.